AMBIENCE OF A CENTER FOR PSYCHO-SOCIAL CARE: STRUCTURAL FACTOR OF THE THERAPEUTIC PROCESS - Janaína Quinzen Willrich; Valquíria Lourdes Bielemann; Fabieli Gopinger Chiavagatti; Luciane Prado Kantorski; Luana Ribeiro Borges (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927977 Aim: to grasp the importance of a Psychosocial Care Center ambience and its relation to the therapeutic process in mental health. Method: this qualitative study was conducted as a case study, comprised a fourth generation evaluation, which was constructivist, and responsive technique with a hermeneutic dialectic approach. The instruments for data collection were semi-structured interviews with the professional team, users and family. All the interviews were recorded. Results: it is clear that the construction of a comfortable environment that invests in the production of subjectivities is a tool to enhance the psychosocial rehabilitation process. And that is the meeting between users and staff, which builds emotional bonds and this is the key component that describes the environment. Conclusion: ambience in mental health humanizes the territories of meetings between users and staff, and that is crucial to build therapeutic relationships.